Understanding India’s Energy Sector: Players, Policy Framework and Challenges (International Journal of Scientific Research and Management (IJSRM), 2015)
Numerous policy reforms over the past 20 years have shifted India’s energy sector from a predominantly government-owned system towards one based on market principles, offering a more level playing field for both public and private sectors. The goal of providing energy access to the entire population led to wellmeaning policies designed to protect the poor, but resulted in a system of untargeted producer and consumer subsidies that prevent a more thorough implementation of a well-functioning and financially sound energy sector. The major objective of this paper to study the policy framework regarding Indian energy sector and secondary objectives are to explain the current status of Indian energy sector and also the challenges faced by this sector. It concluded that around 67 percent of non renewable sources of energy have been used in energy sector so that the pressure is on the non renewable resources.